Gelatin as an ingredient in food and pharmaceutical products: an Islamic perspective - Shah, Harmen; Yusof, Faridah (AENSI Publications, 2014)
Islam is one of thevarious religions on the face of this earth which has categorized the type of foods suitable for human consumption. Thus, the integral concept of Islam that governs the quality and sanctity of food is halalantayyaban i.e; lawful and pure.Gelatin, an animal by-product owing to its gelling property finds immense application in the processing and manufacturing of various foods and pharmaceutical products. But the question is whether the source of gelatin is halal or non-halal. The studies show that a major proportion of gelatin supplied globally comes from pig. Pertaining to this data, the majorMuslim population is under threatas Islam prohibits the consumption of pork in any form except to save one‟s life under life threatening condition which Allah SWT clearly mentions inQuran.This paper points out the situations under which the gelatine inspite of being from halal sources becomes haram.It also attempts to highlight the concept of fiqhistihalah and its process. The paper further focuses on the issues related to gelatin in food and pharmaceutical industry and discusses the legal aspects assigned towards the regulation and monitoring of halal and non-halal products specially the halal food quality standards in Malaysia.